Phenotypic characterization of rabbit model for aortic valve stenosis: a novel medial calcification paradigm. (14th October 2021) - Anousakis-Vlachochristou, N; Mavroidis, M; Makridakis, M; Miliou, A; Kontostathi, G; Agapaki, A; Mouchtouri, E; Zigouri, L; Konstantinou, G; Lampas, E; Kalogera, S; Vlahou, A; et al.
Abstract: Introduction: Calcific aortic valve stenosis (CAVS) is the result of subtle, chronic inflammation and osteoblastic differentiation. As we lack human specimens of the early stages, reliable and reproducible animal models are needed to facilitate research. We previously demonstrated the ability of a novel rabbit CAVS vitamin D2 toxicity protocol to produce calcification and valve stenosis (1). We sought to characterize the phenotype of the model at the final stage. Methods: Twelve New Zealand Rabbits were randomized 1:1 to control (normal chaw) and experimental group (normal chaw+1% cholesterol+3.500 I.U.s Vitamin D2, in oil in a biscuit) for 7 weeks. Animals were sacrificed and aortic valve cusps were snap frozen or formalin-fixed paraffin embedded. Cusps were then mechanically homogenized in buffer optimized for protein extraction and total protein measured with Bradford method. Part of the extract was subjected to trypsinization, in-gel digestion and untargeted LC-MS/MS. The rest was used to quantitate BMP-2 with total protein-normalized sandwitch competitive ELISA. Thin tissue sections were stained with Masson's trichrome, Von Kossa and H&E. Osteopontin, Bone sialoprotein II (BSPII), tissue non-specific alkaline phosphatase (TNAP) and osteocalcin (OCN) were detected on tissue with immunohistochemistry. Femoral bones from the same animals served as positive controls. Results: Aortic valve cusp demonstrate large areas of collagen degradation and calcification in the medial layer, almost sparing the intima. Osteopontin deposits were colocalized with the calcification area in the media, whereas BSPII, TNAP and OCN were not expressed in the lesion, although present in bones. Similarly, BMP-2 levels were not significantly different between groups (experimental = 43.45 vs controls = 62.75 pg/ml, Mann-Whitney U test p=0.496). Proteomic analysis revealed a set of 96 differentially expressed proteins between cases and controls, interestingly including sortilin, osteonectin, beta-crystallin A2, Matrix Gla protein, Na/H exchanger 3, V-type H ATPase subunit D, Y-box binding protein. Conclusion: The novel rabbit vitamin D2 toxicity protocol leads to excessive medial calcification of the aortic valve, with overexpression of osteopontin but without other classic markers of CAVS. Proteomics analysis reveals novel pathways with pathophysiological implications for the model and medial calcification. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Hellenic Cardiology Society, Hellenic Heart Foundation